2021
DOI: 10.1038/s41398-021-01667-2
|View full text |Cite
|
Sign up to set email alerts
|

proBDNF expression induces apoptosis and inhibits synaptic regeneration by regulating the RhoA-JNK pathway in an in vitro post-stroke depression model

Abstract: Brain-derived neurotrophic factor (BDNF) plays an important role in the pathophysiology of post-stroke depression (PSD). However, the precise function and potential mechanism of proBDNF, the precursor form of BDNF, are unknown. In our study, a PSD-like model was established by treating neuronal cells with oxygen-glucose deprivation and corticosterone. We found that the protein proBDNF levels were significantly higher in the cortex and hippocampus in the PSD group than in the control group, suggesting that proB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…More recently, hippocampal glutamate metabolism disorder was found to be induced by treatment with aluminaNPs via activating IFN-γ/ASK1/JNK signaling pathway [ 72 ]. More importantly, the RhoA-JNK pathway can be activated after proBDNF binds to the p75 NTR receptor, which in turn induces oxidative damage and promotes apoptosis, thus affecting synaptic plasticity [ 41 , 78 ]. Therefore, our evidence implies that the activation of proBDNF-RhoA signaling by aluminaNP infusions is an important factor for spatial memory deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, hippocampal glutamate metabolism disorder was found to be induced by treatment with aluminaNPs via activating IFN-γ/ASK1/JNK signaling pathway [ 72 ]. More importantly, the RhoA-JNK pathway can be activated after proBDNF binds to the p75 NTR receptor, which in turn induces oxidative damage and promotes apoptosis, thus affecting synaptic plasticity [ 41 , 78 ]. Therefore, our evidence implies that the activation of proBDNF-RhoA signaling by aluminaNP infusions is an important factor for spatial memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that aluminaNPs can cause oxidative stress and inflammatory events in mouse brains [ 7 , 40 ]. At cellular levels, activation of proBDNF signaling after binding to its receptor p75 NTR plays a major role in neuronal apoptosis and the formation of synaptic plasticity through the activation of the downstream RhoA pathway [ 41 43 ]. Together, these findings pointed to significant disruptions to neuronal function within the hippocampus, leading to the prediction that they may underlie at least some of the spatial learning deficits and memory disorders observed following the aluminaNP exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mature BDNF, pro-BDNF was also detected in the culture supernatants. Pro-BDNF has the opposite effect to mature BDNF: it induces apoptosis and inhibits proliferation [ 87 , 88 , 89 ]. Moreover, several studies have shown that excessive BDNF concentration led to downregulation of the high-affinity receptor TrkB [ 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BDNF was found to be triggered by brain injury as part of the neuroprotective response following a stroke (Kokaia et al, 1998). Moreover, pro-BDNF plays a role in apoptosis following its binding to the p75NTR receptor, which aggravates post-stroke depression (PSD) (Yang et al, 2021). These results indicate that regulation of the BDNF signaling pathway has the potential to treat brain injury after a stroke.…”
Section: Brain-derived Neurotrophic Factor and Brain Injury Following...mentioning
confidence: 98%